RELATIONSHIP BETWEEN WORK LIFE QUALITY AND SUBJECTIVE FATIGUE AMONG NURSES EMPLOYED IN LATGALE REGION HOSPITALS - Deklāva, Liāna; Skrodere, Māra; Fokina, Olga; Vilka, Lolita; Millere, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Quality of health care, safe working environments, sufficient care staff and adequate remuneration in our rapidly changing world are one of the biggest health care challenges. Quality of working life is a reciprocal process between hospital management and nurses in order to simultaneously improve the staff's holistic well - being, working conditions and the effectiveness of hospital work and care. The impact of internal and external factors in the quality of working life can be directly or indirectly related to subjective fatigue for working nurses. The aim of the study is to find out the connection between the quality of working life of nurses working in Latgale region and subjective fatigue. 219 nurses in the Latgale region participated in the study. There were used two research tools: Job quality assessment questionnaire and Individual strength/fatigue questionnaire. In the study descriptive statistical method is used. Using the non-parametric method and the correlation of Spirmen's rank, the relationship between quality of work and subjective fatigue of nurses is determined. The study concluded that there is a link between quality of work life and subjective fatigue (r = -0.375; p<0.001). The result is theoretically and practically applicable in the hospital to improve the quality of work life for nurses.